Mitigating systematic errors for single frequency GPS receivers employing a penalized least squares methodology - Alves, Daniele Barroca Marra [UNESP]; Monico, João Francisco Galera [UNESP] (My University, 2006)
Among the positioning systems that compose GNSS (Global Navigation Satellite System), GPS has the capability of providing low, medium and high precision positioning data. However, GPS observables may be subject to many different types of errors. These systematic errors can degrade the accuracy of the positioning provided by GPS. These errors are mainly related to GPS satellite orbits, multipath, and atmospheric effects. In order to mitigate these errors, a semiparametric model and the penalized least squares technique were employed in this study. This is similar to changing the stochastical model, in which error functions are incorporated and the results are similar to those in which the functional model is changed instead. Using this method, it was shown that ambiguities and the estimation of station coordinates were more reliable and accurate than when employing a conventional least squares methodology.
Keywords: Least squares approximations; Mathematical models; Multipath propagation; Satellites; Signal receivers; Stochastic control systems; Systematic errors; Atmospheric effects; Global Navigation Satellite System; Precision positioning; Semiparametric models; Global positioning system